PEMBATALAN AKTA NOTARIS AKIBAT ADANYA PENYALAHGUNAAN KEADAAN (MISBRUIK OMSTANDIGHEDEN) STUDI PUTUSAN STUDI PUTUSAN NOMOR 214/PDT.G./2014/PN.JKT SEL jo.143/PDT/2016/PT.DKI JO.1359 K/PDT/2017 - AINI NIZARNI RANGKUTI (Journal Law of Deli Sumatera, 2021)
Undue influence is a factor that limits or interferes with the existence of free will to determine the agreement between the two parties who make the agreement. Therefore, when the situation occurs, there is a defect of will experienced by a person. Abuse of state can occur in three criteria such as state of economic advantage, psychological advantage and emergency advantage. This study has three problems, namely: how undue influence can be carried out in the case between Agus Susanto (Plaintiff I) et al against Lisa Juliana Tanjung (Defendant I) et al based on the consideration of the Supreme Court Decision Number 59 K/Pd/2017, how is the position of a notary as parties who do not support the Sale and Purchase Binding in the case between Agus Susanto (Plaintiff I) et al against Lisa Juliana Tanjung (Defendant I) et al based on the consideration of the Supreme Court Decision Number 1359 K/Pdt/2017, what are the legal consequences for the cancellation of the sale and purchase agreement in in the case between Agus Susanto (Plaintiff I) et al against Lisa Juliana Tanjung (Defendant I) et al based on the consideration of the Supreme Court's Decision Number 1359 K/Pdt/2017. This normative juridical research uses a statute approach and a case approach. Sources of data used in this study is secondary data collected by library research techniques. Undue influence became the basis for filing a sale and purchase agreement between Agus Susanto (Plaintiff I) et al. against Lisa Juliana Tanjung (Defendant I) et al. The cancellation of the agreement was initiated based on the Decision of the DKI Jakarta High Court Number 143/Pdt/2016/PT.DKI, then confirmed by the Supreme Court Decision Number 1359 K/Pdt/2017. The position of the notary as a party who does not support the Plaintiff of Sale and Purchase between Agus Susanto (Plaintiff I) et al with Lisa Juliana Tanjung (Defendant I) should not place the Notary Defendants such as Notary Marina Soewana (Defendant II). Several agreement deeds issued by Defendant II have actually been canceled by Agus Susanto (Plaintiff I) et al with Lisa Lusiana Tanjung (Defendant I) as the party who promised in the deed of agreement, thus there is no lawsuit if Plaintiff I et al withdraw Defendant II in their lawsuit only sue for canceled promises. The legal consequences of the cancellation of the sale and purchase agreement in the case between Agus Susanto (Plaintiff I) et al against Lisa Juliana Tanjung (Defendant I) et al are no longer legally binding. Therefore, the sale and purchase is considered to have never existed and a plot of land and building on the right of Building Use Rights Certificate Number 621/Petukangan Utara belongs to Agus Susanto (Plaintiff I) et al. Keywords: Undue influence, defective wills, Notary deed